Combined effect of using steel fibers and demolition waste aggregates on the performance of fly ash/slag based geopolymer concrete - Lakew, Asfaw Mekonnen; Canpolat, Orhan; Al-Mashhadani, Mukhallad M.; Uysal, Mucteba; Nis, Anil; Aygormez, Yurdakul; Bayati, Mohammad (TAYLOR & FRANCIS LTD, 2023)
Developing sustainable construction products has been showing a rising trend recently. Geopolymer composites are remarkable binding materials fabricated based on recycling and sustainability. In this paper, an experimental investigation was conducted to study some mechanical and durability characteristics of steel fiber-reinforced fly ash/slag-based geopolymer concrete (GPC) with different proportions of recycled coarse aggregate. Steel fiber-reinforced geopolymer concrete mixtures incorporating recycled coarse aggregates of up to 40% at the interval of 10% were prepared, and the mixtures without recycled coarse aggregate were used as reference samples. The steel fiber ratio of 0.3% and 0.6% were used and the combined effect of steel fiber and recycled coarse aggregate on the geopolymer composites' behavior regarding strength properties, sulfate resistance, elevated temperature resistance, abrasion resistance, and freezing-thawing resistance was addressed. A significant improvement in strength properties was observed in steel fiber reinforced recycled aggregate geopolymer concrete with increasing fiber content; however, the strength properties of geopolymer concrete were decreased with the increase of recycled coarse aggregate amount. Also, the properties such as abrasion resistance, resistance to elevated temperature, sulfate resistance, and freeze-thaw resistance were improved with the addition of steel fiber. It indicates that the synergetic effect of steel fiber and recycled aggregate helps to produce ecologically sound geopolymer concrete with good engineering properties and durability characteristics that will bring sustainability to the concrete sector. Generally, the results show that the recycled coarse aggregate ratio of up to 30% and 0.6% of steel fiber can be considered an ideal combination to make geopolymer concrete with better overall properties.
Keywords: Geopolymer; fly ash; slag; recycled coarse aggregate; steel fibers; strength properties; durability properties; BLAST-FURNACE SLAG; MECHANICAL-PROPERTIES; RECYCLED AGGREGATE; HIGH-STRENGTH; ASH; BEHAVIOR; COMPOSITES; METAKAOLIN; EVOLUTION; Engineering